Oblicz :
a) (-3)x0,2=
b)6x(- 1 trzecia)=
c)(-1,3)x(-2)=
d)(-9)x(-1 druga)=
e)(-2 siódme)x7 dwunastych=
f)(-12):6=
g)(-4):(-8)=
h)3,2:(-2)=
i)(-3 czwarte) : 1 czwartą =
j)(-0,1) do potegi 2=
k)(-2)do potegi 3=
l)(-1 druga)do potęgi 4=

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-01-14T15:20:11+01:00
A) (-3)x0,2=-0,6
b)6x(- 1 trzecia)=-2
c)(-1,3)x(-2)=2,6
d)(-9)x(-1 druga)=4,5
e)(-2 siódme)x7 dwunastych=1/6 (jedna szósta)
f)(-12):6=-2
g)(-4):(-8)=1/2 (jedna druga)
h)3,2:(-2)=-1,6
i)(-3 czwarte) : 1 czwartą =-3
j)(-0,1) do potegi 2=0,01
k)(-2)do potegi 3=-8
l)(-1 druga)do potęgi 4=0,0625
2010-01-14T15:30:25+01:00
A) (-3)x0,2= -15
b)6x(- 1 trzecia)= 2
c)(-1,3)x(-2)= 2,6
d)(-9)x(-1 druga)= 4,5
e)(-2 siódme)x7 dwunastych= -1 szósta
f)(-12):6= -2
g)(-4):(-8)= 0,5
h)3,2:(-2)= -1,6
i)(-3 czwarte) : 1 czwartą = -3
j)(-0,1) do potegi 2= 0,01
k)(-2)do potegi 3= -8
l)(-1 druga)do potęgi 4= 1 szesnasta

Pozdrawiam ;)